Loss of histone H3 trimethylation on lysine 27 and nuclear expression of transducin‐like enhancer 1 in primary intracranial sarcoma, DICER1‐mutant. Issue 2 (9th November 2020) - Alexandrescu, Sanda; Meredith, David M; Lidov, Hart G; Alaggio, Rita; Novello, Mariangela; Ligon, Keith L; Vargas, Sara O
Abstract : Aims: Primary intracranial sarcoma, DICER1 ‐mutant is a recently described central nervous system tumour with specific genomic and DNA‐methylation profiles. Although some of its histological features (focal spindle‐cell morphology, intracytoplasmic eosinophilic granules, and focal heterologous differentiation) are common across most reported cases, the presence of significant histological variability and the lack of differentiation pose diagnostic challenges. We aim to further define the immunoprofile of this tumor. Methods and results: We reviewed the clinical history and performed immunohistochemistry for glial fibrillary acidic protein, oligodendrocyte transcription factor 2, SOX2, SOX10, S100, histone H3 trimethylated on lysine 27 (H3K27me3), desmin, myogenin, CD99, epithelial membrane antigen (EMA) and transducin‐like enhancer of split 1 (TLE1) on six primary intracranial sarcomas, DICER1 ‐mutant, with appropriate controls. Targeted exome sequencing was performed on all cases. The sarcomas showed diffuse ( n  = 4), mosaic ( n  = 1) or minimal (≤5%, n  = 1) loss of H3K27 trimethylation and nuclear TLE1 expression ( n  = 6). Four had immunohistochemical evidence of myogenic differentiation. SOX2, SOX10, S100 and EMA were negative; CD99 expression ranged from focal cytoplasmic ( n  = 4) to crisp diffuse membranous ( n  = 2). One tumour had focal cartilaginous differentiation. Similar immunohistochemical findings were observed in a pleuropulmonary blastoma (albeit with focal TLE1 expression), a DICER1 ‐related pineoblastoma, and an embryonal tumour with a multilayered rosette‐like DICER1 ‐related cerebellar tumour. Targeted exome sequencing confirmed the presence of pathogenic biallelic DICER1 mutations in all tumours included in this study. Conclusion: We conclude that H3K27me3 and TLE1 immunostains, when utilised in combination, can be helpful diagnostic markers for primary intracranial sarcoma, DICER1 ‐mutant.